COMMUNICATION TECHNOLOGY AND MICRO SMALL MEDIUM ENTERPRISES FOR ENHANCING EXPORT FROM INDONESIA - Wiradinata, Irvan (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
Despite the numerous international digital trading platforms such as eBay, Amazon, and Shopee Export, which can facilitate the business-to-consumer (B2C) business, fewer MSMEs entrepreneurs in Indonesia utilize these. Many MSMEs were merely utilizing email and WhatsApp as the primary communication tools to communicate with their overseas clients. The lack of employing other forms of communication tools or digital trading platforms raises questions. This research, therefore, aims to examine the likelihoods of improving the international online trading platform that use by Indonesia’s entrepreneurs. The research objective is to examine the present communication tools used by entrepreneurs as well as to reveal the communication obstacles that occur during international trade. To obtain the narrative of current international business realm in Indonesia MSMEs industry, a qualitative study performed: literature study, case study, and in-depth interview. This research uses several theories (i.e., diffusion of innovation, contextual design, elaboration likelihood model, motivation, uncertainty reduction, and general system) to examine how invention in trading platforms may shape the export-oriented business process. This research reveals several key results, such as the need to establish an export-focused trading platform that can provide overseas buyer pools, and language as one of the primary communication barriers to perform export. A further challenge for academicians, developers, and governments is to establish a trading platform to enhance export sales which can encounter the buyers pools and language barrier.